The psychometric properties of the Portuguese version of the Personality Inventory for DSM-5 - Pires, R.; Ferreira, A. S.; Guedes, D. (Scandinavian Journal of Psychology, 2017)
The DSM-5 Section III proposes a hybrid dimensional-categorical model of conceptualizing personality and its disorders that includes assessment of impairments in personality functioning (criterion A) and maladaptive personality traits (criterion B). The Personality Inventory for the DSM-5 is a new dimensional tool, composed of 220 items organized into 25 facets that delineate ?ve higher order domains of clinically relevant personality differences, and was developed to operationalize the DSM-5 model of pathological personality traits. The current studies address the internal consistency (study 1), the test-retest reliability (study 2) and the criterion validity (studies 3 and 4) of the Portuguese version of the PID-5 in samples of native speaking psychology students. Results indicated good internal consistency reliabilities and good temporal stability reliabilities for the majority of the PID-5 traits. The correlational pattern of the PID-5 traits with two measures of personality was in accordance with theoretical expectations and showed its concurrent validity.